2013
DOI: 10.1016/j.ydbio.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor GATA4 is required for follicular development and normal ovarian function

Abstract: Sex determination in mammals requires interaction between the transcription factor GATA4 and its cofactor FOG2. We have recently described the function of both proteins in testis development beyond the sex determination stage; their roles in the postnatal ovary, however, remain to be defined. Here, we use gene targeting in mice to determine the requirement of GATA4 and FOG2 in ovarian development and folliculogenesis. The results from this study identify an essential role of the GATA4 protein in the ovarian mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 66 publications
4
50
0
Order By: Relevance
“…Consistent with this expression pattern, different genetic mouse models have begun to illuminate the complex and essential roles played by this transcription factor in the very first steps of gonadal development and later, for male and female fertility (Kyrönlahti et al 2011a,b, Manuylov et al 2011, Bennett et al 2012, Efimenko et al 2013, Hu et al 2013, Tevosian 2014. While these studies clearly established the essential nature of GATA4 in reproduction, understanding how GATA4 accomplishes these tasks, i.e., identifying its target genes and thus its mechanism of action, remains incomplete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this expression pattern, different genetic mouse models have begun to illuminate the complex and essential roles played by this transcription factor in the very first steps of gonadal development and later, for male and female fertility (Kyrönlahti et al 2011a,b, Manuylov et al 2011, Bennett et al 2012, Efimenko et al 2013, Hu et al 2013, Tevosian 2014. While these studies clearly established the essential nature of GATA4 in reproduction, understanding how GATA4 accomplishes these tasks, i.e., identifying its target genes and thus its mechanism of action, remains incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…These crucial functions in early mammalian gonadogenesis necessitate not only GATA4 but also a functional cooperation between GATA4 and its transcriptional partner Friend of GATA 2 (FOG2/ZFPM2; Tevosian et al 2002, Manuylov et al 2008. The requirement for GATA4 protein in testis and ovary is maintained during later fetal development and into adulthood, as several different groups have reported that loss of GATA4 at these stages is associated with disrupted cord formation and impaired spermatogenesis in the testis (Kyrö nlahti et al 2011a, Manuylov et al 2011, and impaired granulosa cell proliferation, theca cell recruitment, and a failure of follicular development ultimately leading to reduced fertility in the adult female (Kyrö nlahti et al 2011b, Bennett et al 2012, Efimenko et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…At embryonic day (E) E10.5-E11.5, Gata4 is already expressed in the somatic cells of the developing genital ridges (Defalco et al 2011, Buganim et al 2012. At E13.5, Gata4 expression becomes sexually dimorphic; in the testis, expression is notably upregulated in Sertoli cells and reduced to some extent in interstitial cells, whereas strong-to-moderate GATA4 expression is observed in the majority of ovarian somatic cells (Heikinheimo et al 1997, Viger et al 1998, Anttonen et al 2003, Manuylov et al 2008, Efimenko et al 2013. A similar pattern of Gata4 expression has been reported in rats (Lavoie et al 2004).…”
Section: Expression Of Gata Genes In Reproductive Organsmentioning
confidence: 99%
“…i) Sf1Cre-mediated loss of Gata4 Efimenko et al (2013) used Sf1Cre-mediated gene targeting to determine the requirement for GATA4 and FOG2 in ovarian development and folliculogenesis. The results from this study identified an essential role for the GATA4 (but not FOG2) in the ovarian morphogenetic/differentiation program.…”
Section: Gata Proteins In Ovarian Developmentmentioning
confidence: 99%
“…The depletion of the follicular pool in a GATA-4 deficient ovary results in the formation of ovarian cysts and sterility [6].…”
Section: Introductionmentioning
confidence: 99%